PENGARUH CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA OLEH CEO BARU - Sirait, Christine Priskayani H.; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi, 2015)
Earnings management by the new CEO can be reduced with the implementation of good corporate governance, in particular through the supervision of the board of commissioners and the audit committee. This study aims to provide empirical evidence about the influence of proportion of independent board of commissioners and audit committee, financial expertise and activity to earnings management by the new CEO. This study was done at the manufacturing companies listed in Indonesia Stock Exchange that do CEO turnover at the period 2008-2012, with a total sample of  36 companies taken with purposive sampling. Based on the results of data analysis by using  multiple linear regression, the study found  negative influence from the proportion of independent board of commissioners and audit committee to earnings management by the new CEO. Financial expertise and activity of the board of commissioners and audit committee of proven does not give influence over earnings management.
Keywords: corporate governance, board of commissioner, audit committee, earnings management, CEO turnover